Soviet Plane at Pearson Air Field - Washington State University Vancouver Library; http://library.vancouver.wsu.edu/
The Soviet Russian plane arrived in Vancouver after a record breaking transpolar flight from Russia. The first non-stop flight over the North Pole. 3x5 in.